Efektivitas Bahan Ajar Berbasis Etnomatematika terhadap Hasil Belajar Matematika Siswa Madrasah Ibtidaiyah - Latifah Nuraini; Fernia Setyowati (Dawuh Guru: Jurnal Pendidikan MI/SD, 2023)
The purpose of this research is to develop ethnomathematics-based flat building teaching materials. The type of research used is Research and Development (R&D) which refers to the ADDIE model. The data collection techniques used are interviews, questionnaires, and comprehension achievement tests or Pre-test and Post-test. The results of this development research are in the form of ethnomathematics-based flat building teaching materials that meet the feasible criteria with the results of material expert validation obtained 87.5%, teaching material expert validation experts obtained 86.25% and learning experts obtained 92.5%. The results of the student response questionnaire to ethnomathematics-based teaching materials were 95.5%. The t-test results obtained a sig value of 0.00 <0.05, meaning that H0 is rejected and H1 is accepted, meaning that there is a significant difference between before and after using ethnomathematics-based teaching materials. Based on the average value of the Pre-test 38.5 and the average value of the Post-test 88, 1 shows a significant increase so it can be concluded that teaching materials have proven effective in improving math learning outcomes.